The method of integrated assessment of boars and sows on the quality of offspring - Войтенко, С. Л. (Scientific Progress & Innovations, 2017)
The main approaches to the integrated evaluation of boars and sows on the quality of offspring in the conditions of a farm (farm) are covered. It is offered to determine the value of boars and sows not only on the fattening and meat characteristics of their offspring, but also on their own productivity of the latter. The sequence of selection of animals for their testing in conditions of the farm according to their own productivity, fattening and meat characteristics with a score for each of the characteristics is described. For a comprehensive evaluation of boars and sows on the quality of offspring offered to use the developed evaluation index, which is based on the average value of all the tests for testing the characteristics of descendants. Offered new method for estimating boars and sows on the quality of offspring will make it possible to estimate not only breeding pigs but hybrid and local ones, to apply a uniform method for estimating the animals of the main herd in farms of different categories, to dispense with pigs' control stations and determine the value of boars and sows in the quality of offspring based on the developed evaluation index.